Answer:
(x, y) = (6, -2)
Explanation:
Sometimes this solution method is called "addition" or "elimination." You want to multiply one or both equations by a value or values that make the coefficients of one of the variables be opposites. Then when you add the equations, the result is an equation without that variable. (One variable has been eliminated.)
Multiply the first equation by -2 to make its x-coefficient the opposite of that in the second equation. Then add the two equations:
-2(3x +3y) = -2(12)
-6x -6y = -24
Add the second equation ...
(-6x -6y) +(6x +11y) = (-24) +(14)
5y = -10 . . . . . simplify
y = -2 . . . . . . . divide by 5
__
3x +3(-2) = 12 . . . . . substitute into the first equation
3x = 18 . . . . . . . . . . add 6
x = 6 . . . . . . . . . . . . divide by 3
The solution is (x, y) = (6, -2).